(untitled) (The Research of Medical Science Review, 2025)
Background: Reproductive-age women often have thyroid nodules and uterine fibroids. Both have been researched separately, but their relationship is unclear. Both disorders may be caused by oestrogen and progesterone abnormalities. Few studies have linked thyroid nodules to uterine fibroids in Azad Kashmir. Objective: To find out the correlation between thyroid nodules and uterine fibroid among reproductive-age women of Azad Kashmir Methodology: In the Radiology department of District Head Quarter Hospital, Kotli, 196 people participated in the study. Four months were spent on a non-probability random sampling investigation. The study comprised reproductive-age women with uterine fibroid, lower pelvic discomfort, interrupted menstrual periods, and informed consent. Women having a history of thyroid cancer, on medication therapy for other cancers, or who refused permission were excluded. The study diagnosed uterine fibroids and thyroid nodules using an ultrasound machine with a curvilinear transducer frequency range of 2-5 MHz and a high-frequency linear frequency range of 7-14 MHz. Results: The average fibroid size was 46.28 mm (±24.87) in length and 41.20 mm (±23.32) in width, while thyroid nodules exhibited a mean length of 7.49 mm (±7.37) and width of 6.69 mm (±6.68). Hypoechoic fibroids (92.9%) and mixed-echogenicity thyroid nodules (45.9%) were predominant. Significant correlations were observed between the echogenicity of fibroids and thyroid nodules (p < 0.05). Conclusion: The study concluded a significant correlation between hyperechoic fibroids and thyroid nodules underscores the shared pathophysiological mechanisms, potentially estrogen-driven, that link these conditions. By integrating hormonal profiling and advanced imaging into routine care, clinicians can enhance diagnostic accuracy and therapeutic outcomes.